Asupan zat gizi makro dan mikro pada anak sekolah dasar yang stunting di Kota Bengkulu - Kusdalinah Kusdalinah; Desri Suryani (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2021)
The Lack of intake of macro nutrients such as energy, protein, and micronutrients such as zinc, iron, calcium, and vitamin A, especially during the growth period will disrupt the growth process of a child which has an impact on stunting. The purpose of this study was to determine the characteristics of respondents and the relationship between macro and micro nutrient intake and stunting in elementary school (SD) children in Bengkulu City. The research design was cross-sectional with cluster sampling. The sample consisted of 82 elementary school children who were stunted in the Teluk Segara District, Bengkulu City. Data collection was carried out by interview and SQ-FFQ. Data processed in computerized. Data analysis using correlation test. The average energy intake was 783.5 kcal, protein 28.3 grams, carbohydrates 103.1 grams, calcium intake 198.1 mg, while the median value for fat intake was 36.7 grams, zinc 3.1 mg, iron 4 mg, and vitamins. A 201.6 mcg. All of these nutrient intakes are very low when compared to the recommended nutritional adequacy rate for school-age children. There is no relationship between macro and micro nutrient intake and stunting in elementary school children in Bengkulu City (p > 0,05). In conclusion, the intake of both micro and macro nutrients is still low in elementary school children and does not show an association with the incidence of stunting.